SYSTEMATIC LITERATURE REVIEW: ANALISIS PEMAHAMAN DAN MISKONSEPSI ENERGI POTENSIAL GRAVITASI PADA PESERTA DIDIK SEKOLAH DASAR - Alpita Noviyanti; Febby Deca Lestari; Afridha Laily Alindra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Understanding the concept of gravitational potential energy in elementary school science education is crucial for helping students grasp the relationship between force, motion, and energy in everyday life. However, various studies indicate that students still struggle to understand the concept of gravitational potential energy and often hold misconceptions. This study aims to analyze students’ level of understanding of the concept of gravitational potential energy, identify the forms of misconceptions that occur, analyze the factors causing learning difficulties, and examine effective learning strategies to help students understand the concept of gravitational potential energy. This study employed the Systematic Literature Review (SLR) method, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data sources were obtained from Google Scholar, Garuda, and SINTA, covering publications from 2021 to 2025. The results of the study indicate that students’ low level of understanding is influenced by a lack of variety in teaching methods, minimal use of concrete materials, and a lack of active student engagement in the learning process. In addition, misconceptions frequently arise regarding the relationship between an object’s mass, gravitational force, and potential energy. Learning strategies such as the use of teaching aids, laboratory experiments, problem-based learning, collaborative learning, and environment-based learning have proven effective in improving elementary school students’ understanding of the concept of gravitational potential energy. Therefore, teachers need to implement innovative, interactive, and contextual science instruction to make learning more meaningful and enhance students’ conceptual understanding.